Landscape Archeology from a geosystemic perspective: the Piracanjuba archaeological site, municipality of Piraju, state of São Paulo, Brazil - Daves, Larissa Figueiredo (2021)
Studies on the relationship between society and the environment in past time frames have shown the relevance of interdisciplinary research between Geography and Archeology. Based on the theoretical grounds of Landscape Archeology, this study investigates the Piracanjuba archaeological site, a Guarani lithoceramic site, located by the middle course of the Paranapanema River, in the municipality of Piraju, state of São Paulo, Brazil. Within the perimeter of the archaeological site under study, four anthropogenic soil patches (ASPs), also known as indigenous black earth, were identified. In terms of results, the study produced an analysis of the environment according to the horizontal (geofacies and geotopes) and vertical (geohorizons) geosystemic concepts, examining the site’s cartographic representation and spatialization as to its relationship with relevant characteristics of the physical-geographic complex of the studied area. This therefore contributes to further landscape analyses of archaeological sites, based on geoindicators, within past time frames. The heterogeneous stratification units evinced the distinguishing features of the studied environments according to the height of each vegetation stratum and their slope sinuosity and steepness towards the water body of the Paranapanema River. The analyses of the anthropogenic soil patches revealed, by means of thermoluminescence, disparity in the dating of the ceramic fragments found in ASP 1 reaching back to 1520 AD, and in the ASP 2 to 1355 AD, probably pointing to two periods of occupation of the archaeological site area.